A Further Case of Larsen's Syndrome: Clinical and Genotypic Challenges in Diagnosis - Arora, Veronica; Pal, Swasti; Kulshreshtha, Samarth; Verma, Ishwar C. (Journal of Pediatric Genetics, 2020)
Larsen's syndrome is characterized by dislocation of multiple large joints, digital anomalies, craniofacial dysmorphism, and short stature. In this paper, we describe a case of a 5-month-old boy with a triad of cardinal features in association with other signs. The diagnosis was confirmed by exome sequencing, which led to the identification of a novel missense variant NM_001457.4:c.4928C > G (p.Ala1643Gly) in the FLNB gene. We describe the role of protein modelling for the establishment of pathogenicity of this variant. We also outline the challenges in genetic diagnosis due to variable expressivity of the variant and discuss the clinicogenetic profile of previously reported patients with Larsen's syndrome in India.
Keywords: Larsen's syndrome; variable expressivity; VUS; protein prediction